2012
DOI: 10.2528/pier12022603
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Carbon Nanotubes on Inter-Digitated Metal Electrode for Switchable Nanophotonic Devices

Abstract: Abstract-This paper reports the modeling and characterization of interdigitated rows of carbon nanotube electrodes used to address a liquid crystal media. Finite Element Method modeling of the nanotube arrays was performed to analyze the static electric fields produced to find suitable electrode geometry. A device was fabricated based on the simulation results and electro optics characteristics of the device are presented. This finding has applications in the development of micron and submicron pixels, precise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…It depends on time (experiment duration) as well as on the geometrical arrangement of microelectrodes in the array. Interdigitated microelectrode arrays (IDA) have more advantageous geometry in comparison to microband electrodes [ 29 31 ]. Chronoamperograms of various types of IDA have been measured using ferrocene in acetonitrile solution as test system.…”
Section: Theory Of Mass Transport At Microelectrode Arraysmentioning
confidence: 99%
“…It depends on time (experiment duration) as well as on the geometrical arrangement of microelectrodes in the array. Interdigitated microelectrode arrays (IDA) have more advantageous geometry in comparison to microband electrodes [ 29 31 ]. Chronoamperograms of various types of IDA have been measured using ferrocene in acetonitrile solution as test system.…”
Section: Theory Of Mass Transport At Microelectrode Arraysmentioning
confidence: 99%
“…From the literature review, a potential solution is by using a combined dielectric lossy base layer with RH-PMA as the final structure to enhance its microwave absorption in the lower frequencies. This base layer can be fabricated using carbon-based materials such as carbon nanotubes (CNTs), graphite, and graphene due to their unique material properties such as conductivity, dielectric, physical, and mechanical properties [15,21]. For instance, CNTs offer favourable EM characteristics such as good microwave absorption and high-electrical conductivity [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The integration of separated clusters happen when the concentration of nanotubes approaches a certain critical value. As a result in the system spreading (infinite) cluster is formed, which leads to appearance of the electric contacts between external electrodes in such a compound [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Experimental studies [1] have shown that the conductivity in nanotube polymeric and ceramic matrix materials follows a percolation-like behavior.…”
Section: Introductionmentioning
confidence: 99%